Corbiculidae in the Pantanal: history of invasion in southeast and central South America and biometrical data - Callil, C. T.; Mansur, M. C. Dreher (Amazoniana, 2002)
The chronology of the invasion by Corbicula of the Central and the eastern part of South America is revised based on the literature and museum collection records. The occurrence of Carhiculu largillierfi (PHILIPPI, 1844) and Corbicula flumine (MULLER,1774) are reported for the first time for the northern Part of the Pantanal of Mato Grosso, at the upper part of the Paraguay River. a tributary of the large Paraná Basin. Corbiculidae were sampled at three different localities, on the banks of the Cuiabá River, near Cuiabá. capital de Mato Grosso State.
Keywords: Corbicula